Alcohol consumption, smoking, and weight loss outcomes: findings from a 12-month digital lifestyle intervention - Wu, Emma R.; Joki, Anu; Venäläinen, Mikko S.; Suojanen, Laura-Unnukka; Pietiläinen, Kirsi H.; Ahola, Aila J. (Oxford University Press (OUP), 2026)
To investigate associations between alcohol consumption, smoking, and weight loss outcomes over a 12-month digital lifestyle intervention, the Healthy Weight Coaching. Weight, height, and waist circumference were self-reported at baseline, followed by weekly weight and quarterly waist circumference reporting. Interpolated weights were used to calculate body mass index at 3, 6, 9, and 12 months. At these timepoints, relative changes from baseline in weight and waist circumference were calculated. On web-based questionnaires, participants reported alcohol consumption (frequency, single-session dose) and smoking (status, daily dose, start age, end year). Participants were categorized as abstinent, low-risk drinkers, and risky drinkers (men: >14 units/week or >6 units/occasion; women: >7 units/week or >5 units/occasion), and as current, former and non-smokers. At baseline, of the 1719 participants (83.3% women, median age 51 years, body mass index 39.1 kg/m2), 20.9% reported abstinence and 16.2% risky drinking, while 12.1% and 22.3% were current and former smokers, respectively. Alcohol consumption decreased over the program, driven by reductions among baseline risky drinkers. Among baseline non-drinkers, increased alcohol intake over 12 months was linked to smaller waist circumference reduction (weekly dose, B = 0.762, P = 0.005; single-session dose, B = 1.168, P = 0.020). Instead, among baseline risky drinkers, cutting alcohol intake was linked to greater weight loss (weekly dose, B = 0.062, P = 0.034; single-session dose, B = 0.321, P < 0.001), and larger waist circumference reduction (single-session dose, B = 0.381, P = 0.031). Higher number of pack-years was associated with attenuated waist circumference reduction (B = 0.059, P = 0.002). Addressing alcohol consumption and smoking may improve weight loss outcomes in digital lifestyle interventions. The trial is registered at clinicaltrials.gov (Clinical Trials Identifier NCT04019249).